Freedom from Religious Persecution Act of 1998: Report together with additional and dissenting views including cost estimate of the Congressional Budget Office to accompany H.R. 2431 - Archer, Bill; Gilman, Benjamin A. (Report, 1998)
Pt. 1: Mr. Gilman, from the Committee on International Relations, 105th Congress, 2nd Session, April 1, 1998. - 35 S. - (REPT. 105-480 Pt. 1); Pt. 2: Mr. Archer, from the Committee on Ways and Means, 105th Congress, 2nd Session, May 8, 1998. - 24 S. - (REPT. 105-480 Pt. 2); Pt. 3: Mr. Smith, from the Committee on the Judiciary, 105th Congress, 2nd Session, May 8, 1998. - 29 S. - (REPT. 105-480 Pt. 3)